Spatial autocorrelation analysis and the social organisation of crop and herd management at Çatalhöyük. (11th July 2022) - Hodder, Ian; Bogaard, Amy; Engel, Claudia; Pearson, Jessica; Wolfhagen, Jesse
Abstract: This article uses spatial autocorrelation analysis in order to explore the social organisation of crop and herd management at the Neolithic site of Çatalhöyük in south-central Turkey. Evidence for spatial clustering across the settlement is sought at different scales (house, neighbourhood, radial wedge, sector, sub-mound) in the different periods of occupation from Early to Late. The data used are sheep carbon and nitrogen isotopes, densities of weed species in archaeobotanical assemblages and the densities of weed species in sheep dung. The results are interpreted in relation to existing work both on crop and herd management and consumption at Çatalhöyük and on the social organisation of the settlement. Complex nested and cross-cutting social groupings shared many aspects of production and consumption activities across the site resulting in limited spatial clustering of values. The impacts of taphonomic factors on these results are considered. Especially by the Late period of occupation at Çatalhöyük, there is some evidence of distinct labour and consumption organisation linked to houses and house groupings.